Readiness of the Kenyan public health sector to provide pre-referral care for severe paediatric malaria - Amboko, B; Machini, B; Githuka, G; Bejon, P; Zurovac, D; Snow, RW (Wiley, 2022)
Objective: To assess readiness among primary public health facilities in Kenya to provide pre-referral antimalarials for severe malaria.